Analysis of High Levels of Urine Proteins as a Sign of Impaired Kidney Function in Communities Around a Nickel Mining Industry in Morosi District, Southeast Sulawesi (Epidemiology, Biostatistics, and Public Health, 2024)
The study is proposed to analyse the influence of individual and environmental factors on protein urine levels as a parameter for impaired kidney function in the community around Nickel mining industry in Morosi Sub-District, Southeast Sulawesi Indonesia. This quantitative study used a cross sectional study design. The population was people in 3 villages around the nickel mining industry aged 20-59 years. The sample size was 61 people using simple random sampling technique. Independent variable was age as representation of individual factor and environmental factors including house condition, water quality, waste management and household liquid waste. Protein urine as a parameter for impaired kidney function as the dependent variable. Data was collected by questionnaire and taking urine samples. Data were analysed using the multinomial logistic regression test with a significance level of 95%. The results show that the determinant of proteinuria levels in communities around the Morosi nickel mining industry was age (p=0.038
Keywords: Kidney disease; age; water; environment; waste; liquid